Inconsistency between the General Theory of Relativity and the Experimental Results of Faraday’s Unipolar Inductor - Konstantinos Patrinos (New Frontiers in Physical Science Research Vol. 4, 2022)
The non-inertiality of the rotating system of Faraday’s unipolar generator forces us to address this problem using the principles of the general theory of relativity. The purpose of this study is to compare the theoretical quantitative estimates of induced electromotive force with the experimental results obtained from the corresponding measurements. The theoretical elaboration of this issue proves that the differences between the results of the general theory in relation to those of the special theory of relativity are some negligible terms, which are due to the non-inertiality of the rotating reference system. This result enables us to consider the theoretical estimates based on special and general relativity as equivalent, with quite satisfactory accuracy. Therefore, a very serious issue of inconsistency between the theory of relativity and the measurements of induced electromotive force emerges, since as already shown in the existing literature, this inconsistency, from the point of view of the special theory of relativity, is already proven.